Scaffolding proteins in membrane trafficking: the role of ELKS - Yu, K.L. (Utrecht University, 2015)
Intracellular membrane trafficking is an essential cellular process that involves cooperation of many factors such as scaffolding proteins, GTPases and SNAREs. These proteins work together to ensure proper delivery of different membrane-enclosed cargoes to specific cellular destinations. In this thesis, we have combined diverse biochemical and molecular genetics approaches to get a better insight in the regulation of intracellular trafficking. In this thesis, we focus on the role of the multifunctional adaptor ELKS and some other scaffolding factors involved in the regulation of intracellular trafficking. Chapter 1 gives an overview on the CAST/ELKS family of proteins and their known functions in different cellular pathways, such as microtubule organization, exocytosis and signaling in vertebrates and in invertebrates. Chapter 2 describes the two pull-down methods that have been widely used as an approach to identify new protein binding partners in combination with mass spectrometry analysis in the later chapters. We also discuss how we use GFP-fusion proteins to validate the interactions using dual-color imaging in fixed and live cells. Chapter 3 dissects the interaction of YIF1A with VAPB in the early secretory pathway and their biological roles in cultured hippocampal neurons. Chapter 4 reveals how two Rab GTPases cooperate with monooxygenase enzyme MICAL-3 through the formation of a cortical complex containing ELKS in the docking and fusion of exocytotic vesicles with the plasma membrane. Chapter 5 extends our understanding of MICAL family proteins. We first focus on the role of MICAL-1 on vesicular trafficking and actin reorganization using a knockout cell model. We then describe novel binding partners of MICAL-3 and highlight a potential role of MICAL-3 in cytokinesis. Chapter 6 describes the generation of ELKS knock-out and GFP-ELKS knock-in mice. We show that while ELKS knockout is homozygously lethal, GFP-ELKS knock-in mice are viable and fertile, demonstrating that different cells and tissues derived from these mice can be used to study ELKS dynamics. Chapter 7 addresses the recruitment and behavior of ELKS at the cell cortex using different cellular models including mouse embryonic fibroblasts and pancreatic islets. Chapter 8 presents a general overview the experimental data presented in the previous chapters and discusses the potential new directions for future research.